Cordyceps cicadae Ameliorates Renal Hypertensive Injury and Fibrosis Through the Regulation of SIRT1-Mediated Autophagy - Cai, Yuzi; Feng, Zhendong; Jia, Qi; Guo, Jing; Zhang, Pingna; Zhao, Qihan; Wang, Yao Xian; Liu, Yu Ning; Liu, Wei Jing (Frontiers in Pharmacology, 2022)
Hypertensive renal injury is a complication of hypertension. Cordyceps cicadae (C. cicadae) is a traditional Chinese medicine (TCM) used to treat chronic kidney diseases (CKD), especially renal fibrosis. Autophagy is described as a cell self-renewal process that requires lysosomal degradation and is utilized for the maintenance of cellular energy homeostasis. The present study explores the mechanism underlying C. cicadae’s renoprotection on hypertensive nephropathy (HN). First, hypertensive nephropathy rat models were established on spontaneously hypertensive rats (SHRs). The expression of fibrosis-related protein and autophagy associated protein were detected in vivo. NRK-52E cells exposed to AngII were chosen to observe the potential health benefits of C. cicadae on renal damage. The level of extracellular matrix (ECM) accumulation was detected using capillary electrophoresis immunoquantification and immunohistochemistry. After treatment with lysosomal inhibitors (chloroquine) or an autophagy activator (rapamycin), the expression of Beclin-1, LC3II, and SQSTM1/p62 were further investigated. The study also investigated the change in sirtuin1 (SIRT1), forkhead box O3a (FOXO3a), and peroxidation (superoxide dismutase (SOD) and malondialdehyde (MDA)) expression when intervened by resveratrol. The change in SIRT1 and FOXO3a were measured in patients and the SHRs. Here, we observed that C. cicadae significantly decreased damage to renal tubular epithelial cells and TGFβ1, α-smooth muscle actin (α-SMA), collagen I (Col-1), and fibronectin (FN) expression. Meanwhile, autophagy defects were observed both in vivo and in vitro. C. cicadae intervention significantly down-regulated Beclin-1 and LC3II, and decreased SQSTM1/p62, showing an inhibition of autophagic vesicles and the alleviation of autophagy stress. These functions were suppressed by rapamycin, and the results were just as effective as the resveratrol treatment. HN patients and the SHRs exhibited decreased levels of SIRT1 and FOXO3a. We also observed a positive correlation between SIRT1/FOXO3a and antifibrotic effects. Similar to the resveratrol group, the expression of SIRT1/FOXO3a and oxidative stress were elevated by C. cicadae in vivo. Taken together, our findings show that C. cicadae ameliorates tubulointerstitial fibrosis and delays HN progression. The renoprotection was likely attributable to the regulation of autophagic stress mediated by the SIRT1 pathway and achieved by regulating FOXO3a and oxidative stress.